Cells : amazing forms and functions - Young, John K. (New York : F. Watts, 1990)
Explores the various cells in the human body and describes how each is best suited to carry out its particular function.
Includes bibliographical references (p. 108) and index.
Booklist.
School Library Journal.
7.6
7.6
7-10.
Keywords: Cells -- Juvenile literature; Cytology -- Juvenile literature; Cells; Cells